DNA Barcode na identificação de Peixes de Bico explorados comercialmente: uma abordagem forense - Rodrigues Junior, Carlos Egberto [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The billfish are oceanic pelagic species often caught by the tuna fleet and with great interest of sport fishing. This group of fish has specific legislation prohibiting the marketing and export of two species, Kajuikia albida e Makaira nigricans, in Brazil. DNA barcode is a universal system of molecular identification based on a sequence of mitochondrial DNA cytochrome oxidase subunit I (COI) of about 650 base pairs, serving as an identifying genomic mark in each species. This system has been used successfully to identify mischaracterized samples illegally marketed, like sample materials from sharks and other endangered species of organisms. The Barcode DNA technique was used to identify billfish marketed in the second largest fishing warehouse in Latin America, the CEAGESP-SP and the international airport of São Paulo, Brazil. 302 samples of billfish were collected during three inspection actions carried out by IBAMA, the executing agency of the national environmental policy. After DNA sequencing procedures it was possible to identify 72 samples (91.14%) by CEAGESP at the level of species, being 21 (29.17%) identified as Xiphias gladius, 44 (61.1%) as Istiophorus platypterus and 7 (8.33%) as Kajikia albida, this latter species determined as a market prohibited in Brazil and considered vulnerable in the list of endangered species of the IUCN and in the official list of species of endangered Fauna - Fish and Aquatic Invertebrates. At the International Airport of Guarulhos it was possible to identify 223 samples (100%), all identified as Xiphias gladius as declared by the exporter and indicated by its NCM (Mercosur Common Nomenclature). Molecular analysis has proven to be an excellent tool to identify billfish in Brazil in different centers such as Guarulhos International Airport and CEAGESP, SP. The identification of the white marlin being illegally traded in CEAGESP demonstrates the ineffectiveness of the current monitoring techniques used and emphasize the need for adopting better public policies for the conservation of the species.

Os peixes de bico são espécies pelágicas oceânicas frequentemente capturadas pela frota atuneira e com grande interesse da pesca esportiva. Este grupo de peixes possui legislação específica que proíbe a comercialização e exportação de duas espécies, Kajikia albida e Makaira nigricans desse grupo no Brasil. O DNA Barcode é um sistema universal de identificação molecular baseado em uma sequência de DNA mitocondrial Citocromo Oxidase subunidade I (COI) de aproximadamente 650 pares de base, servindo como código de barras de DNA de cada espécie. Este sistema tem sido utilizado com êxito para identificar amostras que são comercializadas descaracterizadas e de forma ilegal, como tubarões e outras espécies ameaçadas de extinção. A técnica de DNA Barcode foi utilizada para a identificação de peixes de bico comercializados no segundo maior entreposto pesqueiro da América Latina, CEAGESP, SP e no Aeroporto Internacional de Guarulhos, atualmente o maior volume brasileiro de exportações de peixes de bico no País. Foram coletadas 302 amostras de peixes de bico durante vistorias realizadas pelo IBAMA, 223 no aeroporto e 79 no CEAGESP, órgão executor da política nacional do meio ambiente. Após sequenciamento do DNA foi possível à identificação das espécies de 70 amostras (88,60%) coletadas no CEAGESP, sendo 21 (30%) identificadas como Xiphias gladius, 43 (61,42%) como Istiophorus platypterus e seis (8,57%) como Kajikia albida, esta última de comércio proibido no Brasil, e considerada vulnerável pela lista de espécies em perigo da IUCN e pela Lista Nacional Oficial de Espécies da Fauna Ameaçadas de Extinção - Peixes e Invertebrados Aquáticos. No Aeroporto Internacional de Guarulhos foi possível à identificação de 223 amostras (100%), sendo todas identificadas como Xiphias gladius conforme declarado pelo exportador e indicado pelo seu NCM (Nomenclatura Comum do Mercosul). A análise molecular demonstrou ser uma importante ferramenta na identificação de peixes de bico comercializados no Brasil em diferentes centros como o Aeroporto Internacional de Guarulhos e CEAGESP, SP. A identificação de agulhões branco sendo ilegalmente comercializados na CEAGESP demonstra a ineficácia das técnicas de fiscalização utilizadas e enfatizam a necessidade melhores políticas públicas para a conservação da espécie.
DNA Barcode in the Identification of commercially exploited Billfish: a forensic approach
Keywords: Peixe de bico; Xiphias gladius; Billfish; White marlin; Marlim branco; Espadarte